POTENTIAL APPLICATIONS OF DIETARY Moringa oleifera LEAVES AS GROWTH MODULATOR AND IMMUNOSTIMULANT AGAINST Aeromonas hydrophila FOR FARMED Oreochromis niloticus - Ratchaneegorn Mapanao; Wirat Jiwyam; Wilailuk Khrueanet; Nudtha Nithikulworawong (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2021)
Herbal medicine, including moringa (Moringa oleifera), is widely used as dietary supplementation to enhance growth performance and increase disease resistance in aquaculture. This study aimed to investigate the effects of supplementing moringa leaves on growth performance, hematology and disease resistance of nile tilapia (Oreochromis niloticus) against Aeromonas hydrophila. Fish (38.05 ± 0.83 g) were fed with a commercial feed supplemented by moringa leaves at 0%, 15%, 20%, and 25%, ad libitum, twice a day for eight weeks. Results revealed that 15% moringa leaves supplemented diet gave the highest weight gain, while the specific growth rate was statistically significantly different (p<0.05) among the treatments. Fish fed with 25% supplementation had the highest total red blood cell count and total white blood cell count. All experimental groups had higher values of red blood cells and white blood cells than the control group. The challenge test with A. hydrophila showed that the fish fed with the 25% moringa leaves supplementation diet had the highest relative percentage survival rate. There were no significant differences among the treatment groups. However, the treatment groups had a statistically significant difference with the control group (p<0.05). Results of the present study indicated that supplementation of 15% moringa leaves in diet gave optimal growth performance, while supplementation of 25% moringa leaves in the diet showed the best results in terms of the health of nile tilapia. Moringa leaves supplemented in nile tilapia diet enhanced growth performance and increased disease resistance against A. hydrophila.